2020
DOI: 10.1136/archdischild-2020-320449
|View full text |Cite
|
Sign up to set email alerts
|

Regional ventilation characteristics during non-invasive respiratory support in preterm infants

Abstract: ObjectivesTo determine the regional ventilation characteristics during non-invasive ventilation (NIV) in stable preterm infants. The secondary aim was to explore the relationship between indicators of ventilation homogeneity and other clinical measures of respiratory status.DesignProspective observational study.SettingTwo tertiary neonatal intensive care units.PatientsForty stable preterm infants born <30 weeks of gestation receiving either continuous positive airway pressure (n=32) or high-flow nasal cannu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
(82 reference statements)
1
17
0
Order By: Relevance
“…Preterm infants predominantly use their diaphragm to generate tidal ventilation, and previous EIT studies in infants have shown that the dorsal lung is preferentially ventilated during spontaneous breathing. 9,13,14 The ventral-dorsal shape of the diaphragm is elliptical. Thus, there is greater movement of the dorsal portion of the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preterm infants predominantly use their diaphragm to generate tidal ventilation, and previous EIT studies in infants have shown that the dorsal lung is preferentially ventilated during spontaneous breathing. 9,13,14 The ventral-dorsal shape of the diaphragm is elliptical. Thus, there is greater movement of the dorsal portion of the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…All infants were managed supine to standardise measures however, prone positioning is widely used in NICU, and as we have shown in more recent studies, may improve ventilation patterns. 9,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, overall changes in ventilation including silent spaces (SS), the deviation from the ideal centre of ventilation (ideal minus actual centre of ventilation; CoV i−a ) and the coefficient of variation (CV) were calculated (see figure 1A). 9 15 SS correspond to areas of the lung with little or no ventilation,16 and were calculated in the gravity-dependent (GD) and NGD hemithorax separately ( SS GD and SS NGD , respectively). The CoV i−a indicates a difference in ventilation in respective lung areas (eg, GD or NGD).…”
Section: Methodsmentioning
confidence: 99%
“…7,8 These have shown complex regional ventilation and aeration patterns occurring even in preterm infants considered stable, with relatively low fraction of inspired oxygen (FiO 2 ), on nCPAP. 9 This study aimed to evaluate the feasibility of EIT to describe the regional tidal ventilation (V T ) and end-expiratory lung volume (EELV) patterns in preterm infants during the process of successful elective extubation to nCPAP. To address these aims, we analysed our dataset of EIT measurements from preterm infants made as part of a series of studies conducted between 2008-2013.…”
Section: Introductionmentioning
confidence: 99%